Bài 2: Nhân đa thức với đa thức

♥ Dora Tora ♥

tìm a,b,c,d để với mọi x ta có:

(ax + b)(x^2 + cx + 1) = x^3 - 3x +2

Nguyễn Lê Phước Thịnh
26 tháng 8 2022 lúc 10:37

\(\left(ax+b\right)\left(x^2+cx+1\right)\)

\(=ax^3+ac\cdot x^2+ax+b\cdot x^2+bc\cdot x+b\)

\(=ax^3+x^2\left(ac+b\right)+x\left(a+bc\right)+b\)

Theo đề, ta có: 

a=1; ac+b=0; a+bc=-3; b=2

=>a=1; b=2; c=-b=-2; 1+2*(-2)=-3(luôn đúng)


Các câu hỏi tương tự
Nguyễn Thùy Linh
Xem chi tiết
♥ Dora Tora ♥
Xem chi tiết
Dương Thị Ngọc Hân
Xem chi tiết
Đức Vương Hiền
Xem chi tiết
Đỗ Thuỳ Linh
Xem chi tiết
Nguyễn Thị Thanh Hoa
Xem chi tiết
Nam Trần
Xem chi tiết
Phạm Hồng Linh
Xem chi tiết
Minie Park
Xem chi tiết